Dampak Ekonomi dari Sport Industry, Sport Tourism, dan Sport Science di Era Pasca Pandemi Covid’19 - Titik Purwanti; Kun Ismawati; Ambyah Atas Aji (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This research aimed to determine the effect of sport industry, sport tourism, and sport science to the economy in the era of pasca the covid 19 pandemic, both partially and simultaneously. The sampling technique used is by distributing online questionnaire via google form. The population of the research were students from Soloraya and the sample were 215 respondens. The analysis technique used were descriptive statistic; data quality test which includes validity test and reliability test; classic assumption test which includes normality test, multicollonearity test, and heteroscedasticity test; multiple linear regression analysis; determination coefficient test (R2); t-test; and F-test. The results showed that partially, sport industry variable have a not significant effect to the economy in the era of pasca the covid 19 pandemic, but sport tourism and sport science variables have a positive significant effect to the economy in the era of pasca the covid 19 pandemic. All three variables (sport industry, sport tourism, dan sport science) have a significant effect to the economy in the era of pasca the covid 19 pandemic